Evolutionary ethnobiology - Ferreira Júnior, Washington Soares; Medeiros, Patricia Muniz; Albuquerque, Ulysses Paulino (Ethnobiology and Conservation, 2022)
Ethnobiology is a discipline that deals with understanding the relationship between human beings and biota. The strong interdisciplinary component of ethnobiology allows it to interact with different fields of knowledge. The evolutionary approach in ethnobiology is not completely absent, however it lacks systematization, which has been recently proposed. From this proposal, the evolutionary ethnobiology emerged. This approach studies the relations between human groups and biota from theoretical scenarios of ecology and evolution. Here we present the evolutionary ethnobiology, its key concepts, the theoretical scenarios with which it dialogues.